2015
DOI: 10.1016/j.phrs.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes and gut microbiota: Friend or foe?

Abstract: Type 1 diabetes is a T cell-mediated autoimmune disease. Environmental factors play an important role in the initiation of the disease in genetically predisposed individuals. With the improved control of infectious disease, the incidence of autoimmune diseases, particularly type 1 diabetes, has dramatically increased in developed countries. Increasing evidence suggests that gut microbiota are involved in the pathogenesis of type 1 diabetes. Here we focus on recent advances in this field and provide a rationale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 110 publications
(144 reference statements)
0
36
0
Order By: Relevance
“…The altered gut microbiota, such as the increased abundance of Bacteroidetes, could promote increased intestinal permeability and precede the clinical onset of T1D in animal models and pre‐diabetic and diabetic patients . In fact, the role of the gut microbiota in T1D has been suggested since 1987, and the first study in humans was performed in Finland by using stool samples from four T1D children and four matched controls . They observed that children with T1D had decreased microbiota diversity compared with controls and had a reduction in the Firmicutes : Bacteroidetes ratio (Fig.…”
Section: Type 1 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…The altered gut microbiota, such as the increased abundance of Bacteroidetes, could promote increased intestinal permeability and precede the clinical onset of T1D in animal models and pre‐diabetic and diabetic patients . In fact, the role of the gut microbiota in T1D has been suggested since 1987, and the first study in humans was performed in Finland by using stool samples from four T1D children and four matched controls . They observed that children with T1D had decreased microbiota diversity compared with controls and had a reduction in the Firmicutes : Bacteroidetes ratio (Fig.…”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…In fact, the role of the gut microbiota in T1D has been suggested since 1987, and the first study in humans was performed in Finland by using stool samples from four T1D children and four matched controls . They observed that children with T1D had decreased microbiota diversity compared with controls and had a reduction in the Firmicutes : Bacteroidetes ratio (Fig. ).…”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…More interestingly, if a patient's parent has T1DM, the risk for developing T1DM is 5% and it becomes higher if, among the parents, the father is the diabetic patient [30]. Reports have identified more than 50 genetic risk loci related to T1DM [31] whereas gene variants occurring in a major locus named major histocompatibility complex (MHC) region, also known as human leukocyte antigen (HLA) [32] have similarly been reported to confer between 50-60% of genetic risk associated with T1DM development [33]. The genetic risk is linked with the expression of the gene by affecting the HLA protein ability to bind to antigenic peptides and their antigen presentation to T cells [34].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Recent data indicate that altered gut microbiomes have also implications in the pathogenesis of T1DM as evident by the differences in the gut microbiome profile of T1DM versus healthy controls [33]. Previous studies have reported that as healthy infants approach the toddler stage their microbiomes are seen to be healthier and even more stable.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Along with evidence especially in developed country suggested the development of T1D due to the direct involvement of gut microbiota in immune-mediated pathogenesis [18]. Research studies have proven the role of altered gut microbes in the immunopathogenesis of DM; on the other hand, probiotics which have beneficial role in making healthy gut, have been suggested in DM management [19].…”
Section: Jayaswal Et Almentioning
confidence: 99%